Child malnutrition is a sign of conflict to come: Nigerian study links climate change, food and violence - Mastrorillo, Marina; Song, Chun; Pacillo, Grazia; Villa, Victor (2025)
The pathway from climate change to violent conflict is not simple. There are the obvious immediate effects of global warming like water scarcity and crop failure. But beyond these, climate stress can pave the road to violence through indirect channels – a gradual rise in food insecurity and growing social tensions that set the stage for more armed violence.